2023
DOI: 10.1063/5.0146034
|View full text |Cite
|
Sign up to set email alerts
|

Joule heating and Soret effects on an electro-osmotic viscoelastic fluid flow considering the generalized Phan-Thien–Tanner model

Abstract: This work analyzes the non-isothermal electro-osmotic fluid flow in a microchannel considering the Soret effect and temperature-dependent properties. The constitutive equation that models the fluid rheology corresponds to the generalized Phan-Thien–Tanner (gPTT) model. Temperature and pressure gradients are induced due to the interaction between an ionized fluid and the electrical field imposed at the microchannel's ends, resulting in Joule heating. The temperature-dependent physical properties of the fluid mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…However, the steady EOF of Newtonian fluids in various microcapillary geometric domains, such as the slit parallel plate [7,8], cylindrical capillary [9,10], T-shape [11], rectangular [12,13], annulus [14,15], semicircular [16], and sector [17] microchannel cross-sections, have been the main focus of EOF research. There has been relatively little research done on the EOF of non-Newtonian fluids, especially viscoelastic fluids [18][19][20][21][22][23]. And, just recently, experimental and numerical research revealed that the EOFs of non-Newtonian fluids are time-dependent and exhibit instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…However, the steady EOF of Newtonian fluids in various microcapillary geometric domains, such as the slit parallel plate [7,8], cylindrical capillary [9,10], T-shape [11], rectangular [12,13], annulus [14,15], semicircular [16], and sector [17] microchannel cross-sections, have been the main focus of EOF research. There has been relatively little research done on the EOF of non-Newtonian fluids, especially viscoelastic fluids [18][19][20][21][22][23]. And, just recently, experimental and numerical research revealed that the EOFs of non-Newtonian fluids are time-dependent and exhibit instabilities.…”
Section: Introductionmentioning
confidence: 99%